On the Evaluation of the Shielding Effectiveness of Electrically Large Enclosure - Gifuni, A.; Sorrentino, A.; Fanti, A.; Ferrara, G.; Migliaccio, M.; Mazzarella, G.; Corona, F. (Advanced Electromagnetics, 2012)
The shielding effectiveness (SE) has become afundamental step in testing active or passive electricdevices. The Reverberating Chamber (RC) is a wellestablishedmethod for determining the SE since has theadvantage to expose the material to a more realisticenvironment. In this paper the SEe of electrically largeenclosure with a metallic mesh grid in a RC is evaluated.Enclosures made with metallic mesh are considered. Inparticular, it is shown that the SE of a material is unable toprovide complete information for the SEe of electricallylarge enclosure made with the same material. Moreover,this latter one is related to the loading conditions within theenclosure itself. Measurements accomplished at RC of theUniversità di Napoli Parthenope (formerly IstitutoUniversitario Navale, IUN) confirm the physical soundnessof the proposed approach.